Association of weather factors with the risk of pain exacerbations in people with hip osteoarthritis. (2nd January 2021) - Fu, K; Metcalf, B; Bennell, KL; Zhang, Y; Deveza, LA; Robbins, SR; Ferreira, ML; Hunter, DJ
Abstract : Objectives: Our objective was to evaluate the association of weather factors with the risk of pain exacerbations in people with symptomatic hip osteoarthritis (OA). Method: Eligible participants with symptomatic hip OA were instructed to log on to the study website and complete questionnaires every 10 days and additionally whenever they considered they were experiencing a pain exacerbation (case period) during the 90 day follow-up. Pain exacerbation was defined as an increase of two points in pain intensity on an 11-point numeric rating scale (0–10) during the follow-up compared with baseline. Each case period was anchored to four control periods within a 35 day interval using a time-stratified approach. Weather data were obtained for both periods from the publicly available meteorological database of the Australian Bureau of Meteorology. We examined the association of weather factors across 72 h before the index date with the risk of pain exacerbation, using conditional logistic regression. Results: Among 252 participants recruited, 129 participants had at least one episode of pain exacerbation and were included in the analysis. A significant dose–response relationship was found between average daily temperature variation in the prior 72 h and risk of pain exacerbations (p = 0.04 for linear trend). There was no significant association between maximum daily temperature, minimum daily temperature, relative humidity, precipitation, or barometric pressure and hip pain exacerbations. Conclusion: The overall results suggest that only daily temperature variation among different weather factors was associated with hip pain exacerbations in people with symptomatic hip OA.